In the Current Where Drowning Is Beautiful - Chabitnoy, Abigail (Book collections on Project MUSE., 2022)
"Award-winning poet interweaves English and Alutiiq as a response to the colonial violence and the silencing of indigenous women, in particular the crisis of missing and murdered indigenous women and girls"--